Pengaruh Product Quality Dan Emotional Marketing Terhadap Customer Satisfaction Mempengaruhi Loyalitas Yang Di Moderasi Oleh Social Influence: Pada Brand Skincare - Salsabila, Chika (Innovative: Journal Of Social Science Research, 2025)
This research aims to examine the role of social impact in moderating the relationship between product quality and customer satisfaction, as well as social influence as a moderator between emotional marketing and customer satisfaction in skincare product users. A self-administered survey with a 1-10 scale questionnaire was distributed to 275 respondents using purposive sampling. The majority were women (56.9%) and aged 17-22 years (41.62%). Analysis using Structural Equation Modeling (SEM) revealed that product quality has a significant positive impact on customer satisfaction, and emotional marketing also has a significant positive influence on customer satisfaction. Social impact serves as a reinforcement that strengthens the relationship between product quality and customer satisfaction. Additionally, social influence acts as a moderator, strengthening the relationship between emotional marketing and customer satisfaction. The findings highlight the importance of product quality, emotional marketing, and social influence in enhancing customer satisfaction in the skincare product market.